Physical activity promotion of elderly people as a complex intervention: supportive toolbox. (30th September 2020) - Tillmann, J; Vonstein, C; Rossmann, C; Halbach, S; Acet, S; Schmidt, N; Langosch, C; De Bock, F
Abstract: Issue: In EU countries, almost 20% of the population is aged 65 or older. This longer life expectancy offers many opportunities but health risks as well. Health promotion measures like physical activity are of central importance but only a small proportion of the elderly meets the minimum level of physical activity recommended by the WHO. The project "Ageing in balance" investigates how a complex intervention to promote physical activity in older people can be implemented and facilitated by making practical tools centrally available. Description of the problem: A complex intervention following the steps of an ideal-typical process and combining behavioural and structural preventive approaches is implemented in several model regions in Germany over three years (2019-2021). As a service at the federal level, a toolbox comprising tools for needs assessment, interventions and information on physical activity, project management, legal issues and financing is built up to support the work of local decision-makers. It's evaluated how setting approaches to promote physical activity for elderly people can be successful, which supporting and impeding factors exist and how the process can be supported by a flexible toolbox provided at federal level. Results: Socioeconomically deprived model regions (rural, town, city) were recruited and started to raise awareness and to perform needs assessment. Building of local steering committees and implementing interventions are the next steps. Currently the toolbox contains systematically identified instruments for needs assessment, an intervention database with a newly developed evidence ranking system and several information modules. Lessons: Facilitating promotion of physical activity in the elderly is important as prioritization and resources at local level are often limited. Making the implementation of setting approaches successful and providing the potentially most promising support from federal level is still pioneering work. Key messages: The effort is to build up a flexible support system for local stakeholders to promote physical activity in elderly people. It is evaluated how a complex behavioural and structural prevention effort for elderly people can be implemented.